The Ecological Impacts and Modeling of the Beaver Dam Distribution: A Study on Habitat Characteristics and Environmental Factors in Romania - Alexandru Gridan; Ovidiu Ionescu; Georgeta Ionescu; Ancuta Fedorca; Elena Ciocirlan; Claudiu Pașca; Darius Hardalau (Ecologies, 2025)
Beavers (Castor fiber L.) are recognized as keystone ecological engineers who shape freshwater ecosystems by modifying hydrology, sediment dynamics, and biodiversity. Although beaver populations have recovered across Europe, including Romania, understanding the environmental factors driving their dam distribution remains limited. This study aimed to (i) characterize the physical and compositional features of beaver dams in the Râul Negru basin, Romania, (ii) model the environmental variables influencing the dam distribution using MaxEnt, and (iii) evaluate the implications for broader conservation strategies. Over a five-year survey covering 353.7 km of watercourses, 135 beaver families were identified, with an estimated population of 320–512 individuals. The dam dimensions showed strong correlations with the river slope, channel width, and wetness index. Predictive models based on LIDAR data achieved over 90% accuracy, outperforming SRTM-based models. The results reveal that topographic wetness, flow accumulation, and valley morphology are the strongest predictors of dam presence. These findings contribute to proactive beaver management strategies, highlighting areas of potential future expansion and offering data-driven guidance for balancing ecosystem restoration with human land use, contributing to the development of conservation strategies that balance ecosystem engineering by beavers with human land-use needs in Romania and across Europe.